Proposed Design of Performance Management System ( Case Study: PT XYZ IT Consultant Company) - Darmarisa, Febrina; Adhiutama, Akbar (The Indonesian Journal of Business Administration, 2014)
Abstract- PT Alfa Qwartz is an IT consultant that has been founded since 10 years. During 10 years, PT Alfa Qwartz has gained enough experience and wide channel. In 2012, PT Alfa Qwartz has decreased of profit to half than year before whereas revenue increased. That condition indicated caused by inefficiency business process in company. According to characteristic of a consultant company, human resource like machine for company and give competitive advantage. So, there are strong correlation between inefficiency business process and human resource productivity. Low employee productivity can cause inefficiency business process that can impact to higher operational cost. Low employee productivity closely related to low of employee engagement level and also indicated by high employee turnover during several years. Based on finding fact, it can be concluded that there is lack of human resource management. Beside lack of human resource management, also founded that PT Alfa Qwartz also has lack of process business monitoring that can cause unaligned between business activity and company’s goal. By using Current Reality Tree (CRT) then founded that there is ineffective performance management system in PT Alfa Qwartz. So, PT Alfa Qwartz needs a new performance management system that can create positive influence to business environment and increase employee engagement through Key Performance Indicators (KPI) that can direct business activity align with company’s goal.Keyword: consultant company, performance management system, KPI